Vitamin D Deficiency Is Associated With an Increased Likelihood of Incident Depression in Community-Dwelling Older Adults. - Laird, Eamon; O'Halloran, Aisling; Kenny, Rose; Briggs, Robert (My University, 2019)
Objective: To examine the prospective relationship between vitamin D status and incident depression in a large cohort of nondepressed community-dwelling older people. Design: Longitudinal study examining the relationship between vitamin D levels at baseline (wave 1) and incident depression at 2 and 4 years (waves 2 and 3), embedded within the Irish Longitudinal Study on Aging. Participants with depression at wave 1 were excluded. Logistic regression models reporting odds ratios were used to analyze the longitudinal association of vitamin D categories with incident depression. Analysis was weighted for attrition. Setting and Participants Almost 4000 community-dwelling people aged ≥50 years. Measures: A score ≥9 on the Center for Epidemiologic Studies Depression Scale-8 at wave 2 or 3 was indicative of incident depression. Vitamin D analysis was performed using liquid chromatography-tandem mass spectrometry and deficiency, insufficiency, and sufficiency were defined as <30, 30–50, and >50 nmol/L, respectively. Results: The incident depression group (400/3965) had a higher likelihood of baseline vitamin D deficiency (proportional estimation 19.4) [95% confidence interval (CI) 15.1–24.7] vs [12.4 (95% CI 11.1–14.0); Z = 3.93; P < .001]. Logistic regression models demonstrated that participants with vitamin D deficiency had a significantly higher likelihood of incident depression (odds ratio 1.75, 95% CI 1.24–2.46; t = 3.21; P = .001). This finding remained robust after controlling for relevant covariates including physical activity, chronic disease burden, cardiovascular disease and antidepressant use. Conclusions/Implications: This study demonstrates that vitamin D deficiency is associated with a significant increase in the likelihood of developing depression in later life. These findings are important, given the high prevalence of vitamin D deficiency among older people, the fact that supplementation has a low risk of toxicity or side effects, as well as the significant adverse effect depression can have on functional status and longevity in later
PUBLISHED
Keywords: Depression; vitamin D; vitamin D deficiency; longevity affect; Ageing; AGEING; MENTAL HEALTH